TASTE MASKED CLOPERASTINE HYDROCHLORIDE AND RUPATADINE ORAL DISPERSIBLE TABLETS: FORMULATION DESIGN, DEVELOPMENT, CHARACTERIZATION AND PHARMACOKINETICS STUDY ON WISTAR RATS - ELHABAL, SAMMAR FATHY; TEAIMA, MAHMOUD H.; ALI, YASMIN SHAWQI; EL-NABARAWI, MOHAMED A.; ABDELMONEM, REHAB; ELFAR, NEHAL (International Journal of Applied Pharmaceutics, 2023)
Objective: The main objective of our study was formulating oral dispersible tablets (ODTs) of taste masked cloperastine HCl and rupatadine fumarate by using the lyophilization technique that also enhanced the dissolution of poor solubility of these active substances. Methods: Taking 3 super disintegrants as variables using the Minitab® 18 factorial design method, 27 formulae of ODTs were obtained. The powdered mixtures before direct compression were characterized using Carr’s index, Hausner’s ratio, and angle of repose. The best-powdered formulae were elected to be prepared as ODTs by direct compression to undergo characterization tests such as wetting time, in vitro disintegration test, and in vivo taste masking. According to the Quality by Design QbD approach; the best formula of ODTs prepared by direct compression was elected to be optimized by the lyophilization technique. Incorporating Eudragit E PO®has a major role in the taste masking of lyophilized ODTs. A comparative in vivo pharmacokinetic study of market products of two active substances was carried out for the conventional ODTs, lyophilized tablets, and market products using wistar rats by oral administration of (0.75 mg/ml) for each active substance. Results: The bitter taste was apparently masked in the lyophilized ODTs assessed by in vivo taste masking. The highest Cmax of cloperastine HCl was found at 17.25 mcg/ml in the group of Lyophilized ODTs. Furthermore; the highest Cmax of rupatadine was found at 78.88 mcg/ml in the same group. Conclusion: Lyophilized tablets owned the best bioavailability for both active substances with the highest Cmax compared to market products and ODTs prepared by direct compression.